Long-Term Observations in an Affected Family with Neurogenic Scapuloperoneal Syndrome Caused by Mutation R269C in the TRPV4 Gene - Vill, Katharina; Kuhn, Marius; Gläser, Dieter; Walter, Maggie C.; Müller-Felber, Wolfgang (Neuropediatrics, 2015)
Mutations in the TRPV4 gene, encoding a polymodal Ca2+ permeable channel, are causative for several human diseases, affecting the skeletal and the peripheral nervous system with highly variable phenotypes. We report on a family with two affected individuals. The father clinically suffered from a classical scapuloperoneal syndrome, while the son presented with a severe neonatal onset with congenital respiratory distress, feeding problems and arthrogryposis multiplex. Multi-Gene Panel sequencing by next generation sequencing revealed the heterozygous mutation c.805C > T (p.R269C) in the TRPV4 gene. Long-term observation over two decades showed no relevant disease progression in the father and, after a dramatic neonatal period, a significant improvement in the son who became ambulant with orthoses at the age of 5 years, suggesting a reasonably good prognosis even in cases with severe neonatal onset. Long-term findings in muscle ultrasound correlated with the clinical course, showing stable or even slightly improved findings. Neurography revealed a late-onset sensory neuropathy in the father, which was so far not described in TRPV4 neuropathies.
Keywords: scapuloperoneal syndrome; TRPV4; arthrogryposis multiplex congenita; spinal muscular atrophy; Charcot-Marie-Tooth neuropathy